Obesidade abdominal em mulheres trabalhadoras de turnos e a relação com os padrões alimentares: um estudo de caso-controle - Fröhlich, Carine (Universidade do Vale do Rio dos Sinos, 2016)
Objective: investigate the relationship of abdominal obesity (AO) in female shift workers to dietary patterns (DP). Design: case-control study not paired realized in 2011included 541 females (215 cases; 326 controls), 18 to 53 years old, shift workers in a slaughterhouse in southern Brazil. Cases of AO were defined waist circumference (WC) ≥ 88 cm and control with the WC <88cm. DP was assessed by a food frequency questionnaire (FFQ) containing 53 food items and principal components analysis (PCA). The name of DP was assigned based on higher load factor and nutritional characteristics of foods. The association between AO and DP was obtained by regression non-conditional logistic. Results: three DP called “animal fat/calories”, “snacks/fast-food” and “fruits/vegetables” were identified. The DP “animal fat/calories” had the highest percentage of variance explained (10,97%). Cases had greater adherence to “animal fat/calories” e “fruits/vegetables”, 39,1% e 42,9%, respectively. Controls had greater adherence to DP “snacks/fast-food” (34,7%). Multivariate analysis showed a greater adherence to DP "fruits/vegetables" for the cases (OR = 2.26; 95% CI: 1.30 to 3.93) compared to controls. On the other hand, there was a borderline association with lower adherence to DP "snacks/fast-food" the cases than the controls (OR = 0.60; 95% CI: 0.36 to 1.01). Conclusions: this study identified three DP who described the food intake of female working shifts. The results point to a trend to improved nutrition in working with AO compared with the control group of workers who don’t present this event in health, that is, there is an urgent need for targeted programs and actions to employees towards primary health care.
Keywords: Padrões alimentares; Obesidade abdominal; Circunferência da cintura; Mulheres; Trabalho em turnos; Dietary patterns; Abdominal obesity; Waist circumference; Women; Shift work; ACCNPQ::Ciências da Saúde::Saúde Coletiva